Effects of combination oral care on oral health, dry mouth and salivary pH of intubated patients: A randomized controlled trial. Issue 5 (28th June 2016) - Jang, Chun Sun; Shin, Yong Soon
Abstract : Intubated patients are at risk of oral health problems. Although a variety of oral care regimens for intubated patients have been studied, there is a lack of research on the effects of combination oral care that includes tooth brushing, chlorhexidine and cold water. This open‐labelled, randomized, controlled trial aimed to evaluate the effects of combination oral care on oral health status. Participants aged 20 years and older were recruited on the first day after intubation through convenience sampling in a medical intensive care unit. Random assignment was performed using an internet randomization service. The primary outcome was oral health status. Data were collected during May and June 2013. Participants were randomized to one of two groups (23 intervention and 21 control). The final analysis included 18 patients with combination oral care and 17 in the control group. The intervention group had better oral health (effect size = 1.56), less dry mouth and higher salivary pH than the control group. Any additional burden of providing combination oral care to patients who are mechanically ventilated is worthwhile in terms of clinical outcomes. Summary Statement: What is already known about this topic Oral care is an important nursing practice for critically ill patients who have been intubated. There are practical limitations to assessments of the oral cavity because of the presence of an endotracheal tube and oral airway, as well as concerns about unexpected removal of the tube. There is insufficient evidence regarding the effects of combination oral care that includes tooth brushing, chlorhexidine and cold water. What this paper adds Tooth brushing and swabbing with 0.1% chlorhexidine followed by swabbing with cold water every two hours improved mouth dryness and increased salivary pH. The mouth dryness of patients who were mechanically ventilated was lower than normal. The implications of this paper Combination oral care can be provided to intubated patients in general wards as well as in the intensive care unit. Our findings increase the understanding of critical care nurses regarding the importance of basic nursing care and can be used to design fundamental nursing education programmes concerning effective hygiene care practices.